Analisis Kesesuaian Materi Buku Teks Pelajaran IPA SMP/MTs Kelas IX Semester 1 dengan Tujuan Kurikulum untuk Diintegrasikan dengan Materi Petir - Fitra Maryulis; Ahmad Fauzi; Yohandri Yohandri (Universitas Negeri Padang, 2018)
This research is motivated by a change in curriculum by the progress of education from time to time. One of the facilities in curriculum is a textbook. In the lesson textbooks used must contain the required curriculum structure such as excellence potential, local wisdom and regional needs. One form of local wisdom and regional needs, namely knowledge or understanding of disasters that can be understood through textbooks. Suitable subjects to be integrated with disaster material are IPA. Where, Indonesia is a tropical country that is prone to disasters such as threat of lightning. Science subjects are one subjects that is very suitable to be integrated with knowledge about lightning. This study aims to determine the level of suitability of the science material with the curriculum objectives in science lesson textbooks for SMP/MTs class IX semester 1 and to determine the suitability of the science material in the science textbook of SMP/MTs class IX semester 1 with lightning material. This type of research is descriptive research with a qualitative approach. The population of the data in this study is all grade IX textbooks for SMP/MTs in semester 1 from various publishers in Indonesia and the data samples in this study are class IX books of semester 1 published by publisher 1 and publisher 2. The research data was taken using research instruments with data collection techniques through documentation studies. The results of the study showed that the level of suitability of the Science material with the curriculum objectives in the science grade textbooks of grade IX SMP/MTs semester 1 from publisher 1 with the appropriate criteria (82,294%). Whereas in the subject textbooks publisher 2 with sufficient criteria (72%). Then the level of suitability of the Natural Science material in the grade IX textbooks for SMP/MTs in semester 1 with lightning material for Chapter 1is not appropriate, Chapter 2 is not appropriate, Chapter 3 is not appropriate, Chapter 4 is not appropriate and Chapter 2 is appropriate.